Molecular dynamics simulation insights into the cellular uptake of elastic nanoparticles through human pulmonary surfactant. Issue 37 (25th August 2022) - Supakijsilp, Akkaranunt; He, Jing; Lin, Xubo; Ye, Jian
Abstract : Adjusting inhaled NP elasticity affects their permeability across the human pulmonary surfactant monolayer. Abstract : The interaction between inhaled nanoparticles (NPs) and the pulmonary surfactant (PS) monolayer has drawn significant attention due to its potential in drug delivery design and application for respiratory therapeutics in active and passive cellular uptake pathways. Even though much attention has been given to explore the interaction between NPs and the PS monolayer, the effects of the NP elasticity on the translocation across the PS monolayer have not been thoroughly studied. Here, we performed a series of coarse-grained (CG) molecular dynamics simulations to study active or passive cellular uptake pathways of three NPs with different elasticities through a PS monolayer. The differences between active and passive pathways underly the enhanced targeting ability by ligand–receptor interaction (L–R interaction). In the active or passive cellular uptake pathways, it is found that the increase in stiffness level leads to a higher penetrability of NPs at the same time range. The soft NP has always been withheld inside the PS monolayer due to the lowest level of elasticity, while the other two types of NPs penetrate through the PS monolayer as the simulation progresses toward the end. The NPs in the active cellular uptake pathways take a longer time to penetrate the PS monolayer, resulting in a longer average penetration distance of approximately 40.55% and a higher average number of contacts, approximately 36.11%, than passive cellular uptake pathways, due to the L–R interaction. Moreover, it demonstrates that NPs in active cellular uptake pathways have a significantly higher targeting ability with the PS monolayer. We conclude that the level of NP elasticities has a substantial link to the penetrability in active or passive cellular uptake pathways. These results provide valuable insights into drug delivery and nanoprobe design for inhaled NPs within the lungs.